Biological activities, and phytocompounds of northwest Algeria Ajuga iva (L) extracts: Partial identification of the antibacterial fraction. (August 2018) - Medjeldi, Saida; Bouslama, Lamjed; Benabdallah, Amina; Essid, Rym; Haou, Soumaya; Elkahoui, Salem
Abstract: The use of synthetic food additive and the appearance of antibiotic resistance are at the basis of important human health problems. The substitution of synthetic compounds with new natural substances extracted from plants or microorganisms is therefore the ideal solution to this scourge. The objective of this work was to evaluate the phyto-constituents (polyphenols, flavonoids and condensed tannins), and to test the biological activities (antioxidant, antibacterial and antiviral) of the Ajuga iva (L) aerial part extracts. The antioxidant activity assayed by DPPH method showed an IC50 of 0.43 ± 0.03 mg/mL. Antibacterial activity of aqueous and hydro methalonic extracts was tested against seven pathogenic bacteria ( Staphylococcus aureus, Methicillin Resistant Staphylococcus aureus (MRS), Listeria monocytogenes, Pseudomonas aeruginosa, Bacillus cereus, Escherichia coli and Salmonella enteritidis ) using the diffusion method. A Thin Layer Chromatography-bioautotography-guided was performed, and the isolated antibacterial fraction was identified by CG-MS analysis. Antiviral effect of methanolic extract performed on 4 viruses: Coxsackie Virus type B-3 (CVB-3), Adenovirus type 5 (ADV-5), Respiratory Syncytial Virus type B (RSV-B) and Herpes Simplex Virus type 2 (HSV-2) showed an activity against Coxsackie Virus. As a result of this study, the aerial parts of Ajuga iva (L) extract could be used in the food, cosmetic, medical and health sectors. Highlights: Evaluation of phenolic compounds, and biological activities from Ajuga iva (L) aerial parts. A detrimental effect of A. iva aqueous extract was shown especially on the growth of Methicillin Resistant Staphylococcus aureus (MRS) strain. Appreciable result of TLC bioautography-guided detection of antibacterial fractions. Antiviral effect of Ajuga iva methanolic extract on CVB-3 virus was characterized (IC50, and selectivity index). Partial purification of the antibacterial fraction by GC-MS.